2015
DOI: 10.1017/s2045796015000621
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience and the future for mental health?

Abstract: Psychiatry is in one of its regular crises. It is a crisis of its diagnostic systems despite -perhaps because -of the recurrent claims about the extent of diagnosable 'brain disorders'. It is a crisis of its explanatory systems despite -perhaps because -of its current wager on the brain as the ultimate locus for explanations of mental disorders. It is a crisis of its therapeutic capacities despite -perhaps because -more and more people are making use of its primary mode of intervention focussed on the brain -p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 56 publications
0
26
0
1
Order By: Relevance
“…This approach highlights the need for a more integrative perspective in depression and antidepressant drug research, for which the psycho-pharmacology, neurobiology, psychological, and environmental influences are explored together. Rose 66 suggested that depression should be viewed as arising from more than the brain alone, drawing on an understanding of the whole person, in a particular environment, and with a shaping role for social experiences and milieu. In a similar way, multiple factors need to be considered when understanding antidepressant drug action, its limitations, blocks to successful treatment, and methods to facilitate its effects.…”
Section: Explaining the Delayed Clinical Onset Of Antidepressant Drugsmentioning
confidence: 99%
“…This approach highlights the need for a more integrative perspective in depression and antidepressant drug research, for which the psycho-pharmacology, neurobiology, psychological, and environmental influences are explored together. Rose 66 suggested that depression should be viewed as arising from more than the brain alone, drawing on an understanding of the whole person, in a particular environment, and with a shaping role for social experiences and milieu. In a similar way, multiple factors need to be considered when understanding antidepressant drug action, its limitations, blocks to successful treatment, and methods to facilitate its effects.…”
Section: Explaining the Delayed Clinical Onset Of Antidepressant Drugsmentioning
confidence: 99%
“…Through claims that mental illness is like any other illness -like diabetes, cancer, or kidney disease -MHFA discourses ignore the interdisciplinary critique pointing to psychiatry's absence of bio-marker evidence and objective laboratory tests (Frances, 2013;Rose, 2016). Instead of acknowledging that in fact, "'mental illness' is an illness like no other, or indeed better not conceptualized as an illness at all" (Mills, 2014, p. 27, emphasis in original), MHFA utilizes determinism to help construct mental illness as inevitable, random, and socially and politically meaningless (Albee & Joffe, 2004).…”
Section: Determinismmentioning
confidence: 99%
“…While MHFA training does not equip trainees to provide official diagnosis, MHFA training furthers the psychiatrization of distress by promoting psychiatrybased ways of "seeing and saying" (Foucault, 1994, p. xi;Mills, 2014), diagnostic "styles of thought" (Marsh, 2010, p. 31;Rose, 2000), and diagnostic styles of listening (Anderson, 1997, p. 135), thus fostering diagnostic "sensibilities and sensitivities" (Shotter, 2010, p. v). Despite the stark absence of scientific bio-marker evidence for mental illness (Moncrieff, 2013;Rose, 2016), mental illness diagnoses apply not only to the mind but the whole person; psychiatric diagnoses are totalizing, "fully general," (Gergen, 1994, p. 150), thereby producing a deviant social identity (Goffman, 1963). Oblivious to the social significance of socio-political factors, the DSM classification system dismisses non-psychiatric understandings (American Psychiatric Association, 2013).…”
Section: Essentialismmentioning
confidence: 99%
“…What may be of most benefit is the suggestion of an interdisciplinary approach that provides an intellectual environment to allow the relevant conceptual work to be carried out. As Rose (2016) suggests, we need to ask, 'how does adversity get under the skin? '.…”
mentioning
confidence: 99%
“…Rose (2016) helpfully suggests seeing this view as part of 'formulation' that pulls together peoples reported psychological difficulties and dysphoric experiences in the context of their past and present lives and involves conversations between clinicians, patients and other stakeholders which take account of the persons narrative, their strengths and aspirations. This collective and collaborative view can contribute, not only to our understanding of disorders, but can provide an important means to effectively translate research into practice in psychiatry (Fulford, Bortolotti, & Broome, 2014).…”
mentioning
confidence: 99%